2016
DOI: 10.1016/j.bone.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Towards new material biomarkers for fracture risk

Abstract: Osteoporosis is a prevalent bone condition, characterised by low bone mass and increased fracture risk. Currently, the gold standard for identifying osteoporosis and increased fracture risk is through quantification of bone mineral density (BMD) using dual energy X-ray absorption (DEXA). However, the risk of osteoporotic fracture is determined collectively by bone mass, architecture and physicochemistry of the mineral composite building blocks. Thus DEXA scans alone inevitably fail to fully discriminate indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
(115 reference statements)
3
14
0
Order By: Relevance
“…Other ions can also substitute into the apatite lattice, causing changes to density, for example fluoride (F - ), but these substitutions are thought to be at a much lower level than carbonate. This is consistent with previous research which reported a significant increase in the carbonate content of fracture tissue when compared to age matched non-fracture specimens [39].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Other ions can also substitute into the apatite lattice, causing changes to density, for example fluoride (F - ), but these substitutions are thought to be at a much lower level than carbonate. This is consistent with previous research which reported a significant increase in the carbonate content of fracture tissue when compared to age matched non-fracture specimens [39].…”
Section: Resultssupporting
confidence: 93%
“…Many studies have investigated various parameters associated with bone mineral chemistry, although many report conflicting results. For example, hydroxyapatite (HA) crystallite size has been reported to increase [17, 24, 52, 53], decrease [39, 54] or remain constant [20] with age and in osteoporotic tissue. For the non-fracture group, this study did not demonstrate any change of v TMD with age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in mineral www.nature.com/scientificreports/ content is the most apparent change. However, this is related to a number of modifications in crystallite size and overall crystallinity [40][41][42][43] . This is in part due to the effect of impaired remodelling with age, osteocalcin 43,44 , and changes in hydroxyapatite composition, such as the reduction in a-axis length with the increase in carbonate substitution as well as the increase in overall crystal size 41,[45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…R 2 values indicated in parentheses after arrow when provided. Elastic modulus " (0.53) [89,116] " [89] No relationship [117] " (0) [89] " (0.49) [96] Ultimate compressive strength " (0.89) [89] " [89] " [89] Fracture toughness " [25] (þ0.41 men, þ0.29 women)…”
Section: Stiffness and Strengthmentioning
confidence: 99%